Conference Proceedings: 3rd Annual Society for Claustrum Research Meeting: Location: The Salk Institute for Biological Studies, La Jolla, CA, USA 12 November 2016. Issue 1 (15th December 2017) - Mathur, Brian N.; Reser, David; Smith, Jared B.
EXECUTIVE SUMMARY: Last year, the Society for Claustrum Research held its annual meeting in conjunction with The Salk Institute for Biological Studies, as part of The Salk's celebration of the centenary of Francis Crick's birth. Over 140 registrants took part in an exceptional program of talks and poster presentations presided over by Professor Terrence Sejnowski, the Francis Crick Chair and Head of the Computational Neurobiology Laboratory at the Salk Institute, and Professor Patricia Churchland, Presidential Chair of Philosophy at the University of California, San Diego. Presentations at this year's conference were organized around the theme of 'The Undiscovered Claustrum', with the express intent of addressing Francis Crick's challenging final question about pursuing research on the claustrum: 'What could be more important, so why wait?' [1]. The invited speakers addressed the issue of the undetermined function of the mammalian claustrum, using approaches and model systems which ranged from individual cell recordings to whole-brain imaging in awake human subjects. A key theme which has emerged from these studies is the potential role for the claustrum in selective attention and stimulus salience, as described in the summaries below.